Legume diversification and weed management in African cereal-based systems - Silberg, R.T.; Chimonyo, Vimbayi Grace Petrova; Richardson, R.B.; Snapp, Sieglinde S.; Renner, K. (Elsevier, 2019)
Weed abundance in cereal-based systems has increased in recent years across sub-Saharan Africa for smallholder farmers (cultivating less than two hectares). Smallholders can employ numerous practices to control weeds such as intercropping cereal crops with legumes. We conducted a review to identify the possible mechanisms responsible for weed control according to legume species, weed species and agroecosystem. In the review, we first present common weed species found in specific agroecological contexts. Then, we propose several legume intercrops that provide some control of these species and the reasons why. Finally, we highlight possible social and biophysical tradeoffs for cultivating legumes as a weed control practice in smallholder cereal systems. The review found that while many studies explained the effect a certain legume-intercrop had upon weeds (e.g., emergence rates), few identified the mechanism or mechanisms (e.g., increased predation) behind their control. Without understanding these mechanisms, it is difficult to propose management recommendations for intercropping (e.g., seeding rates). Furthermore, few studies have investigated how legume intercrops affect multiple components of farming systems, including the smallholders that cultivate them. Determining how these components connect and impose tradeoffs for smallholders unveils the drivers (or barriers) behind legume intercropping as a weed control practice.